2018
DOI: 10.3390/md16110448
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Tetramic Acid Derivatives from the Deep-Sea-Derived Fungus Cladosporium sphaerospermum EIODSF 008

Abstract: Seven new unstable tetramic acid derivatives, cladosporiumins I-O (1–7), together with the known analogue cladodionen (8) were isolated from the extract of the deep-sea-derived fungus Cladosporium sphaerospermum EIODSF 008. Their structures were elucidated by spectroscopic analysis, quantum chemical calculations and ECD spectra. Compound 4 was a Mg complex of tetramic acid derivative. In acidic solvent, 4 could change to 1 and 6, and 7 could change to 5. In addition, 1, 5 and 8 existed as two exchangeable isom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…The anti-QS activity of cladosporiumins has not been reported before. In addition, only five compounds, i.e., apiodionen, bripiodionen, vermelhotin, hypoxyvermelhotins and cladosporiumin I(1) [17,18], have the similar skeletons to cladodionen, comprising 2,4-pyrrolidinedione and a pyrene ring or a dihydropyran ring by a double bond. The anti-QS activity of the aforementioned compounds has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The anti-QS activity of cladosporiumins has not been reported before. In addition, only five compounds, i.e., apiodionen, bripiodionen, vermelhotin, hypoxyvermelhotins and cladosporiumin I(1) [17,18], have the similar skeletons to cladodionen, comprising 2,4-pyrrolidinedione and a pyrene ring or a dihydropyran ring by a double bond. The anti-QS activity of the aforementioned compounds has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the growth dynamics of P. aeruginosa PAO1 between the control group and cladodionen-treated groups ranging from 100 µM to 400 µM. Figure S1,S2 and Table S1), the active compounds were identified as a pair of known isomers, cladodionen [17,18]. They were inseparable hybrid polyketide of two E/Z geometric isomers due to spontaneous and rapid isomerization between two forms ( Figure S3).…”
Section: Growth Curve Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…According to Tosi et al (2002) Cladosporium is the most frequently observed genus in association with antarctic mosses. Antimicrobial molecules were reported as produced by representatives of this genus (Zhang et al, 2001;Xiong et al, 2009;Liang et al, 2018), but studies related to the bioactivity of Cladosporium against Xanthomonas are still scarce. In a previous study published by our research group, a representative of Cladosporium showed potencial to inhibit the cell growth of X. citri, X. euvesicatoria and X. axonopodis pv.…”
Section: Discussionmentioning
confidence: 99%